Protocolo para la adaptación en infraestructura y dotación de los servicios de UCI y urgencias de una unidad hospitalaria temporal durante emergencia sanitaria en Colombia (2020)
This directed work is focused on the creation of a clinical protocol that serves as a guide of good practices in the process of opening a temporary hospital unit. It has been developed in compliance with the Ministry of Health and Social Protection together with the National Institute of Health in Colombia, within the framework of generating a plan of preparation and early response to multi-risk scenarios for the standards of equipment and infrastructure. Making available to the health personnel, a proposal of methodology and tools that facilitate the elaboration of their own institutional plans. Forms and some case studies are presented to help the user better interpret the content of the publication, which can be modified or adapted according to the specific requirements of each institution.